Evidence for Skill Level Differences in the Thought Processes of Golfers During High and Low Pressure Situations - Whitehead, Amy E.; Taylor, Jamie A.; Polman, Remco C. J. (Frontiers in Psychology, 2016)
Two studies examined differences in the cognition of golfers with differing levels of expertise in high and low pressure situations. In study 1, six high skill and six low skill golfers performed six holes of golf, while verbalizing their thoughts using Think Aloud (TA) protocol. Higher skilled golfers’ cognitive processes centered more on planning in comparison to lower skilled golfers. Study 2 investigated whether thought processes of golfers changed in response to competitive pressure. Eight high skill and eight moderate skilled golfers, completed a practice round and a competition round whilst verbalizing thoughts using TA. To create pressure in the competition condition, participants were instructed that monetary prizes would be awarded to the top three performers and scores of all golfers would be published in a league table in the club house. When performing under competitive pressure, it was found that higher skilled golfers were more likely to verbalize technical rules compared to practice conditions, especially during putting performance. This shift in cognition toward more technical aspects of motor performance was strongly related to scores on the Decision Specific Reinvestment Scale, suggesting individuals with a higher propensity for reinvestment show the largest changes in cognition under pressure. From a practical perspective, TA can aid a player, coach or sport psychologist by allowing thought processes to be identified and investigate a performer’s thoughts when faced with the pressure of a competition.